Internet-positioning of ecotourist destinations: a comparative analysis - D. S. Bogatyreva; D. A. Ruban (Новые технологии)
The formed graphical Internet-images of the Astrakhan and Lughansk regions as ecotourism destinations appear to be successful comparing to the images of Iceland and the Azores. The problem for on-line marketing of the relevant segment of tourism industry is linked to big amount of information «noise » .